Risk factors and structure of obstetric and perinatal complications in woman, which ill of pyelonephritis (Review of literature and results of own researches) - Golubenko, M. Yu. (Journal of Education, Health and Sport, 2017)
Actuality. Morbidity on a pyelonephritis and complication of motion of pregnancy is the important indicators of the state of health of woman population and baby that determines social meaningfulness of this problem. Research aim. To learn data of anamnesis of illness, life, professional features, domestic and surrounding environment, data of somatic status and to set forth leading risk of origin of placenta disfunction factors for pregnant, patients with a pyelonephritis. Material and methods. On the basis of retrospective analysis there are 20779 histories of illnesses of women, patients with a pyelonephritis, the study of risk of forming of somatic pathology of women and development of placenta disfunction factors is conducted with the aim of warning of complications of pregnancy and pathology of fetal and child. Results of researches. Research of the somatic state of pregnant that are ill a chronic pyelonephritis showed the presence of concomitant pathology in 100% cases, from that the diseases of the cardiovascular system laid down 61,5%, endocrine violations 50,2%, the dyspepsia phenomena and gastroenterology pathology 40,5%. The structure of obstetric, perinatal complications for women with a chronic pyelonephritis (20779 supervisions) included: early toxicosis (65,5%), placental dysfunction (73,3%), an eclampsia (78,3%), threat of abortion (76,1%) and premature luing-ins (56,2%), subzero placentation (76,1%), high water-level (76,7%), gestational anaemia (67,8%), delay of height of fetal (17,1%), chronic fetal distress (21,3%), premature removing layer by layer of placenta (26,3%); in luing-ins: premature outpouring of near of fetal waters (22,4%), weakness of childbirth (72,3%), obstetric bleeding (47,1%); in a puerperium: subinvolution of uterus (26,3%). Conclusion. Thus, executed by us research in relation to the study of morbidity and prevalence of pyelonephritis among pregnant allowed to set the following: placenta disfunction in the period of pregnancy registered oneself in 100% habitants of districts with a row by quality of drinking-water, in 90% patients with cardiovascular pathology, in 62,1% with passion to smoking and on a background considerable gas is muddy air contamination of environment, in 41,9% pregnant, that abuse of alcohol, in 37,9% with an off-grade feed, in 27,6% as a result of chronic stress, chronic fatigueability, influence of microwave irradiation. The above-stated factors are leading risk of origin of placenta disfunction factors for pregnant, with ill of pyelonephritis.